Effectiveness and Safety of Adalimumab in Patients With Very Early-Onset Inflammatory Bowel Disease: A Retrospective Study on Behalf of the Porto Inflammatory Bowel Disease Working Group of European Society for Pediatric Gastroenterology Hepatology and Nutrition - Weintraub, Yael; Collen, Lauren V; Hussey, Seamus; Mitrova, Katarina; Machta, Joseph S; Kang, Ben; Granot, Maya; D'Arcangelo, Giulia; Spencer, Elizabeth A; Kolho, Kaija-Leena; Yeh, Pai-Jui; Sladek, Malgorzata; et al. (Inflammatory bowel diseases, 2025)
BACKGROUND AND AIMS: Patients with very early-onset inflammatory bowel disease (VEO-IBD), with an age of onset < 6 years, can present with severe manifestations and may require biologic therapy. Infliximab and adalimumab are approved for induction and maintenance in pediatric IBD patients but are licensed only above the age of 6 years. Effectiveness and safety data on adalimumab in this patient population are lacking. We assessed the therapeutic response to help close this gap. METHODS: This retrospective study involved 30 sites worldwide. Demographic, clinical, and laboratory data were collected from patients with VEO-IBD who commenced adalimumab therapy before the age of 6 years. RESULTS: Seventy-eight patients (37 Crohn's disease, 26 ulcerative colitis, and 15 with IBD-unclassified) were included. Median age of IBD onset was 2.6 (1.3-4.1) years, with 30 (38.5%) patients diagnosed at age <2 years. Median age at adalimumab initiation was 4.2 (2.8-5.1) years. Adalimumab was used as second-line biologic therapy in 45 (57.7%) patients after infliximab. The median time to last follow-up was 63 (22-124) weeks. Significant improvement in clinical scores, CRP, fecal calprotectin, and weight Z-score were observed by Week 52. Adalimumab durability rates were 61.9%, 48.1%, and 35.6% after 1, 2, and 3 years, respectively. Drug discontinuation rates were not dependent on IBD type, age, prior anti-TNF exposure, or concomitant immunomodulatory treatment. Four (5.1%) patients developed serious infections, including 1 patient with TTC7A deficiency who died following adenovirus sepsis. CONCLUSION: Adalimumab therapy is a viable therapeutic option in patients with VEO-IBD with an acceptable safety profile.
Keywords: VEO-IBD; adalimumab; monogenic IBD; anti-TNF